CRREL report. - Cold Regions Research and Engineering Laboratory (U.S.); Cold Regions Research and Engineering Laboratory (U.S.). Report.
GeoRef ASTIS current awareness bulletin ASTIS bibliography Engineering index energy abstracts Engineering index bioengineering abstracts Engineering index monthly (1984) Engineering index annual (1968) Mode of access: Internet. Formed by the merger of: Technical report - Corps of Engineers, U.S. Army, Cold Regions Research and Engineering Laboratory, ISSN 0149-3833, and: Research report - Corps of Engineers, U.S. Army, Cold Regions Research and Engineering Laboratory, ISSN 0501-5812.